Proceedings of the 2007 SIGCOMM Workshop on Internet Network Management 2007
DOI: 10.1145/1321753.1321772
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing VLAN usage in an operational network

Abstract: In this paper we present a study characterizing VLAN usage in a large-sized campus network. Despite their extensive prevalence in enterprise and campus networks, the usage of VLANs has received little systematic treatment in the research community. Our study is conducted using a whitebox approach, involving data such as router configuration files obtained from network operators, and through iterative interactions with them. Our study shows that the use of virtualization is prevalent to enable users belonging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…While we focus on complexity within an ISP's network configuration, prior works [7,15,18,11] have focused on the causes for complexity in enterprises. These studies found core enterprise network designs to be complex due to the usage of VLANs, routeredistribution commands, and network security and filtering policies.…”
Section: Related Workmentioning
confidence: 99%
“…While we focus on complexity within an ISP's network configuration, prior works [7,15,18,11] have focused on the causes for complexity in enterprises. These studies found core enterprise network designs to be complex due to the usage of VLANs, routeredistribution commands, and network security and filtering policies.…”
Section: Related Workmentioning
confidence: 99%
“…VLAN characterization studies. Garimella et al studied VLAN use in a campus network; they highlighted the prevalence of VLANs, characterized different types of misconfiguration, and showed that routing traffic between proximal hosts but distinct VLANs can result in significantly longer layer-3 paths [8]. In contrast, we study the relationships between IP-layer paths and layer-2 paths, and the effects of this sharing on redundancy and diagnosis.…”
Section: Related Workmentioning
confidence: 90%
“…A few studies [9,11] examined traffic characteristics in enterprises, and other recent work developed models for design and configuration in enterprises [3,7]. Our work adds to these by shedding light on the nature of reachability policies in enterprises.…”
Section: Related Workmentioning
confidence: 92%